Kata selection trends in top-level para-karate competitions: a multi-championship study - Augustovicova, Dusana; Hadza, Radovan; Magyar, Adrian; Van Biesen, Debbie; Hruby, Michal (BMC sports science, medicine & rehabilitation, 2025)
PURPOSE: Para-karate has been gaining popularity rapidly; however, scientific research on the subject remains limited. This study aims to examine the kata preferences at top-level para-karate events and explore the relationship between sport class (type of impairment) and kata selection. METHODS: Data was collected from nine events-four World Para-Karate Championships (2016, 2018, 2021, 2023) and five European Para-Karate Championships (2018, 2019, 2021, 2022, 2023). A total of 906 katas were performed: 567 by males and 339 by females. Descriptive statistics and chi-square tests were used for analysis. RESULTS: Top-level para-karate athletes utilized 62 katas (61%) from the official WKF list (102 katas). The most popular katas were Gojushiho Sho (19.9%), Unsu (11.5%), Kanku Sho (9.5%), Suparinpei (6.7%), and Jion (6.2%). A significant relationship was found between sport class and kata selection (p ≤ 0.05). The most popular kata for K30 was Unsu (15%), while K10 and K21 + K22 classes predominantly chose Gojushiho Sho (16.6% and 30.3%, respectively). CONCLUSIONS: Kata selection for para-karate athletes is influenced by the type of impairment. Intellectually impaired athletes and their coaches often select a single, challenging kata with a balanced fast-to-slow movement ratio, such as Gojushiho Sho, to optimize performance.